Childcare policies in Latin America: A comparative analysis of Chile, Costa Rica, Uruguay y Mexico - LÓPEZ ESTRADA, Silvia (Frontera Norte, 2017)
Governments shape social problems, discourses and the solutions to solve them. In this context, the main goal of this paper is the comparative analysis of childcare policies in the following countries: Chile, Costa Rica, Uruguay, and Mexico. In order to contribute to the debate about childcare in Latin America, in the light of the frame critical analysis, the problem that each policy solves is analyzed and compared, as well as its aims and solutions. The study is based on governmental documents such as plans and programs, as well as on academic and social organizations discourses, and the literature about the topic in the Latin American region.